Discussing "human rights" with the displaced: The use of 'religion' and other discursive devices by displaced sudanese in "human rights" discourse - Bajor, William J. (Campos - Revista de Antropologia, 2001)
The notion of Human Rights can be discussed in an infinite variety of ways. It is a highly politicised notion which is ever-changing and can be utilised in any number of fashions as a discursive tool. This paper focuses on the Human Rights discourse of four displaced Sudanese. Their discourse was intimately connected with a variety of factors; including their understanding of what is currently taking place in Sudan, their ordeal in Sudan before exile, and how they are coping with life as externally displaced Sudanese.